An Evaluation on Anonymity and Known Painters in Byzantine Painting Art - Gülşah Uslu (Art-Sanat)
Most of the mosaic, fresco and icon examples of Byzantine painting art are anonymous. Anonymity is closely related to the devotional intentions of the painters during the copying of the cult images. Icons attributed to St. Luke, the first painter according to Christianity, also concealed the identity of the painter. However, this situation did not prevent all painters expressing their own identities in their works. There are known mosaic masters, fresco and icon painters such as Ephraim, Georgios Kallierges, Angelos Akotantos from Crete, Michael Astrapas and Petrus. These artists are known from church dedication inscriptions and the signatures they leave on their works. Church dedication inscriptions containing the names of artists have survived from all periods of the Byzantine Empire. This situation shows a craft tradition that has been maintained since the Early Byzantine Period. In the 12th century, painters began to leave their prayers and signatures on their works. It became more common in the 14th century. In this study, the reasons for the anonymity seen in Byzantine painting are examined more clearly. The inclusion of the names of the painters in the church dedication inscriptions and their use of signatures were evaluated in terms of social-economic and function.